Association of Tumor Necrosis Factor-α-308 gene Polymorphism with Psoriasis in Babylon Province - Mona N. Aterehi (Journal of Global Pharma Technology, 2017)
Psoriasis is an immune mediated skin disease with wide-world prevalence involves both genders and different age, it a multifactorial disease influenced by genetic and environmental factors. The current study objectives to evaluate the association of Tumor Necrosis Factor-αgenes polymorphism (SNPs) with psoriasis by PCR-RFLP while there serum levels determined by ELISA. Methods case-control study (64) patients with psoriasis and (38) apparently healthy people as control matched with disease group. All samples collected in Marian Medical City in Babylon Province. Polymorphism (SNPs) determined by Polymerase Chain Reaction (PCR), restriction fragment length polymorphism (PCR-RFLP) and DNA sequencing techniques, while there serum levels determined by ELISA .Results this study revealed a significant increasing of TNF-α in patients compare with controls (P<0.01). Also, there a significantly regression between severity of disease and TNF-α serum level (-r=0.49, p=0.0001). Genetically, analysis of the Single Nucleotide Polymorphisms PCR-RFLP genotyping for TNF-α -308 SNP, Genotype distribution in patient were AA 5 (7.81%) ,AG 24 (37.50%) and GG 35 (54.69%) while in control 10 (26.31%), 16 (42.11%) and 12 (31.58%) respectively. Conclusion: The massive majority of single nucleotide polymorphism in the TNF-α gene have a clinical importance concerning psoriasis. There is an interaction among the single nucleotide polymorphism of TNF-α gene and it is serum level.Keyword: Psoriasis, Tumor Necrosis Factor-α polymorphism, PCR-RFLP Polymorphism.